Improving Students’ Speaking Skill Through Learning Cell Method At Eleventh Grade SMAN 1 Palibelo - Fitri Ningsi; Rangga Armansyah (STKIP Taman Siswa Bima, 2018)
The objective of the study is to improve students’ speaking skill at eleventh grade students especially in class XI IPA2 of SMA N 1 Palibelo in academic year 2017/2018 through the learning cell method. The research designed was Classroom Action Research which has four procedures, namely: Planning, Implementing, Observing, and Reflecting. The subjects in this research were the eleventh grade students especially in class XI IPA2 of SMA N 1 Palibelo which has 30 students consisting of six males and twenty-four females students. The researcher used two kinds of research instruments, namely: Observation sheet and Speaking test. This research applied in two cycles. The data shown that both of teacher and students activities were in active level the students’ speaking skill, based on the result observation data gained mean score class of first cycle were 73 and total of students were fulfil the criteria of individual only 17 from 30 students, so that, precentage of learning result were 66,6%. This score have not fulfilled the (KKM) of SMAN I Palibelo, it means that the research was unsuccessful because the target of the success in this study was 85% among the whole member of the eleventh grade of SMAN I Palibelo. So, the researcher should arrange for the second cycle, after doing improvement in second cycle the result of observation data gained mean score of the class were 85,33 and total of students were fulfill the criteria of individual 27 from 30 students, so that, percentage of learning result were 90%. It means that the application of the learning cell method is suitable especially to improve students’ speaking skill.